Enhancing the anti-colon cancer activity of quercetin by self-assembled micelles - Xu, Guangya (Int J Nanomedicine, 2015)
Colorectal cancer, a type of malignant neoplasm originating from the epithelial cells lining the colon and/or rectum, has been the third most frequent malignancy and one of the leading causes of cancer-related deaths in the US. As a bioflavonoid with high anticancer potential, quercetin (Qu) has been proved to have a prospective applicability in chemotherapy for a series of cancers. However, quercetin is a hydrophobic drug, the poor hydrophilicity of which hinders its clinical usage in cancer therapy. Therefore, a strategy to improve the solubility of quercetin in water and/or enhance the bioavailability is desired. Encapsulating the poorly water-soluble, hydrophobic agents into polymer micelles could facilitate the dissolution of drugs in water. In our study, nanotechnology was employed, and quercetin was encapsulated into the biodegradable nanosized amphiphilic block copolymers of monomethoxy poly(ethylene glycol)–poly(ε-caprolactone) (MPEG–PCL), attempting to present positive evidences that this drug delivery system of polymeric micelles is effective. The quercetin-loaded MPEG–PCL nanomicelles (Qu-M), with a high drug loading of 6.85% and a minor particle size of 34.8 nm, completely dispersed in the water and released quercetin in a prolonged period in vitro and in vivo. At the same time, compared with free quercetin, Qu-M exhibited improved apoptosis induction and cell growth inhibition effects in CT26 cells in vitro. Moreover, the mice subcutaneous CT26 colon cancer model was established to evaluate the therapy efficiency of Qu-M in detail, in which enhanced anti-colon cancer effect was proved in vivo: Qu-M were more efficacious in repressing the growth of colon tumor than free quercetin. In addition, better effects of Qu-M on inducing cell apoptosis, inhibiting tumor angiogenesis, and restraining cell proliferation were observed by immunofluorescence analysis. Our study indicated that Qu-M were a novel nanoagent of quercetin with an enhanced antitumor activity, which could serve as a promising potential candidate for colon cancer chemotherapy.